IMPLEMENTASI KURIKULUM DARURAT COVID-19 - Didit Haryadi; Fitri Mahmudah (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
The curriculum is at the heart of education. During the Covid pandemic, the government through the ministry of education and culture is working on making the current learning process run well and smoothly even though learning is carried out remotely or online. The latest policy issued by the Ministry of Education and Culture is an emergency curriculum for education units in special conditions. The objectives of the research on the implementation of this emergency curriculum is to knowing the readiness of the school for implementing the emergency curriculum This research uses qualitative research. This research approach is a case study. This research was conducted at SMP PGRI Taropo. Participants in this study were the principal, vice principal in curriculum, and teachers. Data collection techniques using interviews. Data analysis techniques used the Miles Huberman model and were analyzed using the Atlas.ti software version 8. Based on the results of the analysis, the implementation of the emergency curriculum at SMP PGRI Taropo has four important things in its implementation, namely: (1) Teacher Competency Development; (2) Learning Change; (3) Technology Utilization; and (4) Evaluating Learning Outcome